MANAGEMENT OF ECONOMIC OPPORTUNITIES OF INDUSTRIAL ENTERPRISE - Khakimova , Mamura Shukurullayevna (GOLDEN BRAIN, 2024)
Managing the Economic Opportunities of an Industrial Enterprise" is devoted to the study of methods and strategies aimed at optimizing the use of resources and potential of an industrial enterprise to achieve sustainable economic growth and competitiveness. This topic examines various aspects of management, including market analysis, strategic planning, innovative development and financial management.